Percutaneous Coronary Intervention (Pci) Versus Coronary Artery Bypass Grafting (Cabg) in Multivessel Disease - Akhtar, Nazia; Alali, MHD Munzer Hussin; Darwish, Raghd Mustafa; Gul, Sania Akhtar Akhtar; Aldhaheri, Fatima; VK, Shamna; Zaabi, Hind Al; Elsamani, Abdelslam Hatim; Mohammed, Risalatelislam Babiker Omer; Fikry, Mariam Abdullah; et al. (Archives of Clinical and Biomedical Research, 2026)
Background: Both coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) are recognized revascularization techniques in patients with multivessel coronary artery disease (MVD). The comparison of long-term clinical outcomes of these methods is still up for debate, especially with regard to overall safety, risk of myocardial infarction, stroke, mortality and the need for repeat revascularization. Objective: In patients with multivessel coronary artery disease, the long-term clinical outcomes and safety profile of CABG and PCI were compared in this systematic review and meta-analysis. Methods: Randomized controlled trials (RCTs), long-term follow-up studies and excellent meta-analyses contrasting PCI and CABG in multivessel disease were found through a thorough search of the literature. Randomized trials included in recent meta- analyses served as the basis for quantitative synthesis, and additional trials and follow- up studies were qualitatively incorporated. Major adverse cardiovascular events (MACE) and all-cause mortality were the main outcomes. Myocardial infarction (MI), stroke, repeat revascularization and safety outcomes were examples of secondary outcomes. Random- effects model was used to generate results and the I2 statistic was used to measure heterogeneity. Results: In comparison to PCI, CABG was linked to significantly lower long-term all- cause mortality (pooled OR ≈ 0.73, 95% CI: 0.62–0.86), myocardial infarction (OR ≈ 0.58, 95% CI: 0.48–0.72) and repeat revascularization (OR ≈ 0.29, 95% CI: 0.21–0.41). A small increase in risk of stroke was found for CABG when compared to PCI, although it was not statistically significant (OR ≈ 1.36, 95% CI: 0.99–1.86). For MI and mortality, heterogeneity was minimal, but in case of repeat revascularization, it was significant. Subgroup analysis showed that patients with three-vessel disease and diabetes mellitus benefitted greatly from CABG. Conclusion: When compared to PCI, CABG offers better long-term results for patients with multivessel coronary artery disease, especially when it comes to lower mortality, risk of myocardial infarction and the need for repeat revascularization. These advantages are most noticeable in patients with complicated coronary anatomy and diabetes, which support the current guidelines which recommend CABG for these groups.